The Effect of Service Quality Using the Pakserv Model on Customer Satisfaction at BPRS Bina Amanah Satria KC Bumiayu - Nur Adi Chandrawan; Ubaidillah; Ryan Fahmi Hikmat; Ma’ruf Hidayat (Wealth: Journal of Islamic Banking and Finance, 2025)
Sharia banking is an important element in the development and formation of the Indonesian economy. In facing increasingly complex challenges, companies need to look for creative ideas or the latest strategies to achieve company goals optimally. Quality is an important aspect that customers and potential customers pay attention to, so that strategic efforts to improve and maintain quality become a necessity to maintain service and improve the company's position in the market, including BPRS Bina Amanah Satria KC Bumiayu. The PAKSERV Service Quality Model is considered the best setting for understanding and measuring service quality, which has six variables, namely tangibility, reliability, guarantee, sincerity, personalization, and formality. The purpose of this research is to highlight the importance of BPRS Bina Amanah Satria KC Bumiayu continuing to improve the quality of its services by paying attention to aspects measured through the PAKSERV model. By increasing customer satisfaction, it is hoped that customer loyalty can be strengthened and the image and performance of BPRS Bina Amanah Satria KC Bumiayu in the market can be improved. This research is field research and uses a descriptive quantitative approach. The data collection method was carried out through questionnaires distributed to BPRS Bina Amanah Satria KC Bumiayu customers totaling 190 respondents. The analysis technique used is multiple linear regression using the IBM SPSS statistical program. The research results show that service quality as measured through the PAKSERV model simultaneously has a positive and significant influence between PAKSERV on customer satisfaction. Meanwhile, the partial test results show that the Tangibility, Sincerity, and Personalization variables have a Sig value < 0.05, meaning they do not have a significant effect, and the Reliability, Assurance, and Formality variables have a Sig value > 0.05, meaning they have a significant effect.